Nursing Student Perceptions of Reflective Journaling: A Conjoint Value Analysis. (5th September 2012) - Hendrix, Thomas J.; O'Malley, Maureen; Sullivan, Catherine; Carmon, Bernice
Abstract : This study used a statistical technique, conjoint value analysis, to determine student perceptions related to the importance of predetermined reflective journaling attributes. An expert Delphi panel determined these attributes and integrated them into a survey which presented students with multiple journaling experiences from which they had to choose. After obtaining IRB approval, a convenience sample of 66 baccalaureate nursing students completed the survey. The relative importance of the attributes varied from a low of 16.75% (format) to a high of 23.58% (time). The model explained 77% of the variability of student journaling preferences (r 2 = 0.77 ). Students preferred shorter time, complete confidentiality, one-time complete feedback, semistructured format, and behavior recognition. Students with more experience had a much greater preference for a free-form format (P < .05 ) when compared to students with less journaling experience. Additionally, the results of English as a second language students were significantly different from the rest of the sample. In order to better serve them, educators must consider the relative importance of these attributes when developing journaling experiences for their students.